Upaya Meningkatkan Penjualan UMKM Kuliner Di Desa Krembung Dengan Implementasi Pemasaran Digital Melalui Platform Instagram - Arke, Nadya Ramadhani; Hasanah, Rofidatul; Sari, Dewa Ayu Made Dearwita; Sagala, Maria Tania Agustia; Sani, Sani; Puspitawati, Ika Nawang (Madani: Jurnal Pengabdian Masyarakat dan Kewirausahaan, 2024)
Micro Small to Medium Enterprises (MSMEs) are one of the economic pillars of society in Indonesia. Most people choose MSMEs as their livelihood because of the relatively small capital and fast results. In Krembung Village, many MSMEs have been established in various fields, including culinary, fashion, services, and many more. However, most of the culinary sector still uses conventional marketing. This marketing is considered less effective in this digital era. The method of non KKN T MBKM in this service is by observing MSMEs, creating Instagram accounts and banners, as well as digital marketing training. The result of implementing this service is that culinary MSMEs understand digital marketing and promotions and get an increase in sales after implementing this digitalization.